ANALYSIS OF UKS MANAGEMENT READINESS AND MY HEALTH REPORT BOOKS IN ELEMENTARY SCHOOL OF SURABAYA CITY AND GRESIK DISTRICT - Yuly Sulistyorini; Maulidiyatun Nafiisah; Diah Indriani; Soenarnatalina Melaniani; Mahmudah Mahmudah; Sulvy Dwi Anggraini (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2022)
The School's Health Clinic or Usaha Kesehatan Sekolah (UKS) is used as the unit to carry out health programs, especially in the school environment. The UKS has direct benefits for improving the health of schoolchildren and has great potential in the success of the health promotion program for students. This study aims to determine the management of UKS in Primary Schools in Surabaya City and Gresik District in the aspects of UKS management readiness, aspects of ease in understanding my health report card and the ease of implementing my health report card. This study was a cross-sectional observational study. The data were collected using a questionnaire and analyzed descriptively. Based on the results of the questionnaire analysis, it was still found a number of elementary schools in Surabaya City and Gresik District who are in a condition not ready in the aspects of managing their UKS There are still elementary schools in Surabaya City and Gresik Regency who find it difficult to understand the health report cards for students and also find it difficult to implement student health report cards. The advice that can be given is that schools need to prepare everything, for example, in selecting competent human resources in their fields, seeking readiness for UKS implementation facilities and infrastructure, and coordinating with related sectors such as the Health Office and Education Office related to financial problems in procuring health report cards for students so that all schools in Gresik Regency and Surabaya City can distribute evenly to all students.